Prevalence of canine parvoviral enteritis in pet dogs at Dhaka city of Bangladesh - Roy, Sawrab; Ahmed, Juned; Basit, Md. Shamsul Islam; Ahmed, Sagir Uddin; Alam, Shahrul; Chowdhury, Q M Monzur Kader; Sharma, Binayok; Rahman, Mohammad Sujaur; Popy, Farzana Yeasmin (International Journal of Biological Research, 2018)
Background: Canine parvoviral enteritis is a highly contagious viral disease of dog that can lead to life-threating illness.Objectives: The present study was conducted to determine the prevalence of canine parvoviral enteritis in dogs of Dhaka City Corporation, Bangladesh.Methods: A total of 545 dogs were examined at Dr. Sagir’s Pet Clinics and Research Centre, Dhaka during September 2016 to August 2017. The disease was diagnosed on the basis of clinical history, clinical signs and by CPV rapid Ag kit test.Results: Overall prevalence of canine parvoviral enteritis was recorded as 13.94%. The prevalence of canine parvoviral enteritis varied significantly (p0.05). Male dogs (18.74%) were found to be significantly (p
Keywords: Bangladesh; Canine Parvoviral Enteritis; Dhaka; Dog; Prevalence.